2004
DOI: 10.1007/s00439-004-1082-1
|View full text |Cite
|
Sign up to set email alerts
|

Leukotriene-related gene polymorphisms in ASA-intolerant asthma: an association with a haplotype of 5-lipoxygenase

Abstract: A recent study has demonstrated the possible involvement of a leukotriene C4 synthase (LTC4S) gene polymorphism in ASA-intolerant asthma (AIA) in a Polish population, whereas no significant association was noted in other populations. To investigate the role of genetic polymorphism in AIA development, we screened single nucleotide polymorphisms (SNPs) of the key enzymes involved in arachidonate metabolism, and the cysteinyl leukotriene receptor 1 (CYSLTR1) in a large Korean population with AIA: 93 AIA and 181 A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
114
4
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 125 publications
(121 citation statements)
references
References 31 publications
2
114
4
1
Order By: Relevance
“…However, we could not find any significant associations of this new polymorphism or their haplotypes with AIA patients. Although we did not conduct a functional study of this polymorphism, our findings combined with previous observations (Choi et al 2004) suggest that the two promoter polymorphisms in the LTC4S gene, as well as their haplotypes, do not contribute to the pathogenesis of AIA development in a Korean population.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…However, we could not find any significant associations of this new polymorphism or their haplotypes with AIA patients. Although we did not conduct a functional study of this polymorphism, our findings combined with previous observations (Choi et al 2004) suggest that the two promoter polymorphisms in the LTC4S gene, as well as their haplotypes, do not contribute to the pathogenesis of AIA development in a Korean population.…”
Section: Discussionmentioning
confidence: 56%
“…In contrast, no significant associations were detected in American (Van Sambeek et al 2000), Japanese (Kawagishi et al 2002), Australian (Kedda et al 2004), or Spanish (Isidoro-García et al 2005 populations. We also did not find an association between LTC4S -444A>C and AIA in a Korean population (Choi et al 2004). In this regard, the genetic pathogenesis of AIA might not be explained with a single nucleotide polymorphism (SNP) of LTC4S -444A>C despite the confirmed association in a Polish population.…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…2,4 Overproduction of CysLTs and deficiency of prostaglandin E 2 in bronchial fibroblasts by COX inhibition have been proposed to have crucial roles in AERD development. 4,15 However, along with conflicting results for the associations between polymorphisms of genes in leukotriene and COX pathways [16][17][18] genes on other pathways including bronchial hyperresponsiveness by MHC or structural genes have provided new insights for AERD pathogenesis. 5,19 Therefore, although further replications and functional evaluations are required, our findings on the associations of TAP2 with AERD-related symptoms, particularly with FEV1 decline by aspirin provocation, might provide evidences for the role of the gene in respiratory deficiencies.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported associations of the genetic variations in many genes on the arachidonate, immune response and inflammation pathways, such as leukotriene C4 synthase (LTC4S), 26,27 arachidonate 5-lipoxygenase (ALOX5) 16 and MHC class II, DP beta 1 (HLA-DPB1), 25 with aspirin hypersensitivity in asthmatics. However, conflicting results of the associations between polymorphisms of the genes and AERD have been reported, suggesting that underlying mechanisms of AERD pathogenesis may be more complicated than previously thought.…”
Section: Discussionmentioning
confidence: 99%